(3eYGjjQ GdeMGSHjI hGdGHdGZ GdeGdj GdOhdjI (B:s (3GdLhGfH GdfXQjI hGdYedjI (B/s - (3GHhfUGQ, eMeOs ((3YeGf(B: s (3OGQ hGFd(B, s, 2008)
(3GdGWGQ GdeaGgjej dEYOGO hYQV GdbhGFe GdeGdjIf YQV GdbhGFe GdeGdjI, GdeNRhf, bGFeI GdJOabGJ GdfbOjI, GdSjGSGJ GdeMGSHjI hGdJZjQGJ aj GdJbOjQGJ GdeMGSHjI hGdCNWGA, GdCMOGK GddGMbI dJGQjN GdejRGfjI, YbhO GdGfTGA, VQGFH GdONd, GdJbGQjQ Mhd GdbWGYGJ, GdeeJdcGJ hGdeUGfY hGdeYOGJJ, YbhO GdGjLGQ, GdGjQGOGJ, efGaY GdehXajf, eMGSHI GdefM GdMchejI hGdGaUGM Yf GdeSGYOGJ GdMchejI, BKGQ GdJZjQGJ aj CSYGQ UQa GdYedGJ GdCLfHjI, JcGdja GdGbJQGV, GdGaUGMGJ Yf GdCWQGa PGJ GdYdGbI, GdeMGSHI hGdJbQjQ Yf HQGeL efGaY GdJbGYO, GdbhGFe GdeGdjI GdehMOI hGdefaUdI, GdGSJKeGQGJ aj GdTQcGJ GdRejdI, GdJbQjQ GdeGdj aj GdGbJUGOjGJ PGJ GdJVNe GdeQJaY, GdMUU aj GdeTGQjY GdeTJQcI, GdCOhGJ GdeGdjI, QHMjI GdSge, GdJbGQjQ GdeGdjI GdeQMdjI, GdGfNaGV aj bjeI GdCUhd, GdeNUUGJ GdCUhd hGdGdJRGeGJ GdeMJedI, GdCUhd ZjQ GdedehSI, GdCOhGJ GdeGdjI, GdeeJdcGJ GdGSJKeGQjI, GdRQGYI` JWHjb eYGjjQ GdGHdGZ GdeGdj GdOhdjI dChd eQI, GdeOahYGJ Ydi CSGS GdCSge, GfOeGL GdCYeGd, YbhO GdJCejf, GdCUhd ZjQ GdeJOGhdI GdeMJaX HgG ddHjY hGdYedjGJ GdeJhbYI, GdcTa Yf GdeUGOQ GdeYOfjI GdWHjYjI, hJbjjegG, GdCOhGJ GdeGdjI (B((3GdGaUGM(B)s
Keywords: (3GdJGejfs; (3GdYbhOs; (3GdeMGSHIs